2017
DOI: 10.1016/j.chemosphere.2017.06.104
|View full text |Cite
|
Sign up to set email alerts
|

Spatial distribution and implications to sources of halogenated flame retardants in riverine sediments of Taizhou, an intense e-waste recycling area in eastern China

Abstract: Concentrations and spatial distribution pattern of organohalogen flame retardants were investigated in the riverine surface sediments from Taizhou, an intensive e-waste recycling region in China. The analytes were syn- and anti- Dechlorane Plus (DP), Dechloranes 602, 603, and 604, a DP monoadduct, two dechlorinated DPs and 8 congeners of polybrominated diphenyl ethers (PBDEs). The concentrations of ΣPBDEs, ΣDP, ΣDec600s, and ΣDP-degradates ranged from <100 to 172,000, 100 to 55,000, not detectable (nd) to 1600… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(7 citation statements)
references
References 39 publications
(59 reference statements)
1
6
0
Order By: Relevance
“…The highest total concentration of LCMs in the 23 sediments from the e-waste recycling area was found at R19, which is a location very close to an e-waste recycling base. In the previous reports, the highest ∑PBDE concentrations were detected in the same area . The upstream sites (R1–11, ∑LCMs range: 0.137–1.73 ng/g dw) of the Yongning River had relatively lower concentrations than the downstream sites (R12–23, ND-3.10 ng/g dw), suggesting the adverse effect of this recycling plant (Figure E).…”
Section: Results and Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…The highest total concentration of LCMs in the 23 sediments from the e-waste recycling area was found at R19, which is a location very close to an e-waste recycling base. In the previous reports, the highest ∑PBDE concentrations were detected in the same area . The upstream sites (R1–11, ∑LCMs range: 0.137–1.73 ng/g dw) of the Yongning River had relatively lower concentrations than the downstream sites (R12–23, ND-3.10 ng/g dw), suggesting the adverse effect of this recycling plant (Figure E).…”
Section: Results and Discussionsupporting
confidence: 54%
“…In the previous reports, the highest ∑PBDE concentrations were detected in the same area. 29 The upstream sites (R1−11, ∑LCMs range: 0.137−1.73 ng/g dw) of the Yongning River had relatively lower concentrations than the downstream sites (R12−23, ND-3.10 ng/g dw), suggesting the adverse effect of this recycling plant (Figure 1E). The distributions of nonfluorinated LCMs and fluorinated LCMs in the sediments from the three typical areas are summarized in Figure S4.…”
Section: Spatial Distributions and Concentrations Of 39mentioning
confidence: 97%
“…Dechlorane Plus (DP), a replacement for decabromodiphenyl ether (Deca-BDE), comprises two major stereoisomers (syn-DP and anti-DP) in commercial mixture, and has been widely used in plastic materials, computer connectors, electrical wires, and cable coatings (Wang et al, 2017b;Zhou et al, 2017). The annual productions of DP by OxyChem (USA) and Anpo Electrochemical Co. (China) are ~5000 and 300e1000 ton, respectively (Wang et al, 2017b).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, marginal and open seas are regarded as an important reservoir for DP (Jia et al, 2011;Zhao et al, 2011). Recently, several studies had focused on investigating the concentration and distribution of DP in the environment (He et al, 2014;Zhou et al, 2017;Zhu et al, 2018), but little attention has been paid to an extensive and comprehensive understanding of DP concentrations, fluxes, and budgets in coastal seas. The multi-box mass balance model can be used to predict the fate of POPs in the environment and to gain an appreciation of the relative importance of various fate processes (Mackay et al, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…Dechlorinated DP species were first discovered in the environment in 2008 by Sverko et al Since then, DP derivatives with fewer than 12 chlorines have been observed worldwide in air, sediments, , sewage sludge, , seawater, marine ,,,,,, and terrestrial ,, biota, bird eggs, , human serum , and hair, , placental tissue, breast milk, and dust. , The ubiquitous presence of these related compounds in environmental samples is troubling given that research has shown some degradation products to be more toxic than a parent compound, as is the case for the hydrodechlorinated analogues of the chlorinated pesticides aldrin and mirex …”
Section: Introductionmentioning
confidence: 99%